1991
DOI: 10.1002/chin.199115247
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Conversions of Some Dienes with a Caryophyllane Skeleton in Acidic Media.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Next, we shifted our attention toward exploring the viability of our hDA proposal outlined in Scheme a. The potential dienophile 11 was accessed in two steps from 1 (Scheme b) . Reaction of 11 with 12 under unoptimized reaction conditions provided a mixture of 1′,9‐ epi ‐psiguadial B ( 21 ), and an unassigned minor diastereoisomer, in a combined 23 % yield.…”
Section: Figurementioning
confidence: 99%
“…Next, we shifted our attention toward exploring the viability of our hDA proposal outlined in Scheme a. The potential dienophile 11 was accessed in two steps from 1 (Scheme b) . Reaction of 11 with 12 under unoptimized reaction conditions provided a mixture of 1′,9‐ epi ‐psiguadial B ( 21 ), and an unassigned minor diastereoisomer, in a combined 23 % yield.…”
Section: Figurementioning
confidence: 99%
“…This isomer is not too surprising given the structural similarity between it and b-caryolanol, the principal product generated in the sulfuric acid process. Other reports have shown that 8 can be generated from caryophyllene, either by hydrochlorination/dechlorination 43 or by reaction with mercury acetate. 44 Except for 9, all of the other significant products including 5-7 are the principal hydrocarbon products generated with sulfuric acid.…”
Section: Paper Pccpmentioning
confidence: 99%
“…[25,29,30] Robertson and co-workers treated isocaryophyllene ( 44 ) with sulfuric acid in diethyl ether to obtain α-neoclovene ( 49 ) and tricyclic olefin 37 , which resembles the tricyclic core of the presilphiperfolanols (Scheme 9A). Since these early studies, Collado was able to favor the formation of olefin 37 by employing silica-supported FeCl 3 .…”
Section: Synthetic Studies Toward the Presilphiperfolanol Natural mentioning
confidence: 99%
“…[25b] Further work by Khomenko and co-workers has produced alcohol-containing tricyclic structures that more closely resemble the presilphiperfolanols. [30] Treatment of isocaryophyllene ( 44 ) with fluorosulfonic acid and sulfuryl fluorochloride at −100 °C followed by a careful quenching of the acidic solution led to the formation of tricyclic alchohol 4 in 16% yield (Scheme 9B). The structure was assigned based on 1 H and 13 C NMR studies and confirmed by single crystal X-ray diffraction.…”
Section: Synthetic Studies Toward the Presilphiperfolanol Natural mentioning
confidence: 99%